Implementasi Pos bantuan Hukum di Pengadilan Tata Usaha Negara Banda Aceh - Amin, Mirazani; Iskandar, Hadi; Nuribadah, Nuribadah (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2024)
AbstractLegal Aid Posts have an important role in public services by providing assistance to individuals who need legal assistance. This assistance is not limited to those who are economically disadvantaged, but is also provided to individuals who do not fully understand the judicial process and therefore require the assistance of an advocate to ensure the upholding of their rights and obligations. This service is available to all Indonesian citizens, with the aim of upholding justice for those caught in legal problems. Legal aid organizations play an important role in society by offering solutions at various levels, including consultation and assistance outside the courtroom.This research method includes a type of empirical juridical study, or what is called a field study, namely examining applicable legal provisions and what appears in reality in society. And answer all questions. Empirical juridical studies are legal studies regarding the enactment or application of empirical legal provisions in action in all specific legal events that arise in society.According to this study, it was found that the Legal Aid Post (Posbakum) of the Banda Aceh State Administrative Court has a very important role in providing legal aid services. Even though there are challenges faced, efforts to overcome these obstacles are carried out through various means such as disseminating information, increasing legal knowledge, and creating websites. Through these initiatives, Posbakum strives to ensure that individuals have access to the legal assistance they need, ultimately promoting fairness and fairness in the state administrative justice system.The author's suggestion is that the Chairman of the Banda Aceh State Administrative Court take a transparent and cooperative approach, with the aim of obtaining more precise and reliable information during research. Furthermore, this approach is expected to improve the quality of assistance services provided by Posbakum at the Banda Aceh State Administrative Court as a whole. Going forward, it is very important to closely monitor the performance of Posbakum and effectively introduce or promote to the general public the existence of the Legal Aid Post at the Banda Aceh State Administrative Court, which is specifically designed to serve individuals who need free legal services.